RESULTS OF INTERVENTIONS TO STRENGTHEN PRE, INTRA AND POSTNATAL CARE PRACTICES OF KHMER MOTHERS LIVING IN COASTAL AREAS, BAC LIEU PROVINCE BAC LIEU PROVINCE (Vietnam Journal of Community Medicine, 2021)
This study was conducted to evaluate the results of interventions to increase practice of prenatal, intranatal and postnatal care to Khmer mothers with children aged 0-2 years in Hoa Binh District, Bac Lieu Province, from October 2018 to October 2019. By using Quasi Experimental Study on community intervention, pre-and post-control assessment with a control group. The intervention area was 2 communes (Vinh Hau and Vinh Thinh) in Hoa Binh district and the control area was 2 communes (Long Dien and Long Dien Dong) in Dong Hai district. 1386 mothers have participated in interviews. The mother’s practicing pre/intra/postnatal care indicators were compared by the rates before and after the intervention to evaluate the effectiveness of the intervention. Intervention activities including: training health workers, broadcasting on loudspeaker, hanging signs, distributing leaflets, flipbooks, health workers counseling and group communication for mothers about prenatal, intranatal and postnatal care; using Khmer language in communication materials. As results: all 16 indicators of practice of pre/intra/postnatal care of Khmer mothers after intervention increased compared to before the intervention (p
Keywords: Ante/intra/postnatal care; Khmer ethnic mothers; coastal area